2007
DOI: 10.1039/b607614a
|View full text |Cite
|
Sign up to set email alerts
|

Can ionic liquids dissolve wood? Processing and analysis of lignocellulosic materials with 1-n-butyl-3-methylimidazolium chloride

Abstract: The bulk of the cellulose currently employed by industry is isolated from wood through Kraft pulping, a process which traditionally involves a barrage of environmentally detrimental chemicals and is undeniably 'non-green.' In this report we present a simple and novel alternative approach for the processing of lignocellulosic materials that relies on their solubility in solvent systems based on the ionic liquid (IL) 1-n-butyl-3-methylimidazolium chloride ([C 4 mim]Cl). Dissolution profiles for woods of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
525
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(546 citation statements)
references
References 21 publications
11
525
1
9
Order By: Relevance
“…The high solubility of wood flour in [Cl] À -containing ILs is consistent with reports in the literature (Fort et al, 2007;Kilpeläinen et al, 2007;Li et al, 2008). This may be rationalized by the high solubility of the predominant wood constituent, cellulose, in such solvents.…”
Section: Pretreatment Of Wood Flour In Various Ilssupporting
confidence: 89%
See 1 more Smart Citation
“…The high solubility of wood flour in [Cl] À -containing ILs is consistent with reports in the literature (Fort et al, 2007;Kilpeläinen et al, 2007;Li et al, 2008). This may be rationalized by the high solubility of the predominant wood constituent, cellulose, in such solvents.…”
Section: Pretreatment Of Wood Flour In Various Ilssupporting
confidence: 89%
“…For example, cellulose reconstituted after being dissolved in [Amim][Cl] and [Bmim][Cl] had lower degrees of crystallinity than native cellulose, which resulted in greater accessibility of the polysaccharide chains to cellulases, and thus more facile hydrolysis than was achieved without initial dissolution in and reconstitution from an IL (Dadi et al, 2006(Dadi et al, , 2007Liu and Chen, 2006). More recently, several groups have reported the dissolution of full lignocellulosic materials such as corn stalks, rice straw, bagasse, pine wood, and spruce wood in ILs followed by cellulose hydrolysis with acid or enzymes (Fort et al, 2007;Kilpeläinen et al, 2007;Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Used as a pretreatment regime, ILs have been demonstrated to be effective on a variety of biomass sources, such as switchgrass, corn stalk, rice straw, bagasse, sugarcane, pine wood, maple wood, hardwood red oak, and mixtures of softwoods (Fort et al 2007;Kilpelainen et al 2007;Lee et al 2009;Li et al 2010;Li et al 2008;Singh et al 2009;Sun et al 2009;Tan et al 2009;Trinh et al 2015). They are also becoming more cost-effective as compared to other pretreatment options (George et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Furthermore, many liquid-liquid phase equilibrium systems such as IL/water and IL/ organic solvent systems have been presented; this indicates the possibility of utilizing ILs as reaction or extraction solvents. [12][13][14][15] For example, it has been shown that 1-alkyl-3-methylimidazolium bis(trifluoromethane sulfonyl)amide ([C n mim][NTf 2 ]), a typical hydrophobic IL, can be used for the extraction of aromatic compounds from aliphatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%